Perceived Benefits and Challenges of Ebola Preparation Among Hospitals in Developed Countries: A Systematic Literature Review. (13th August 2019) - Puig-Asensio, Mireia; Braun, Barbara I; Seaman, Aaron T; Chitavi, Salome; Rasinski, Kenneth A; Nair, Rajeshwari; Perencevich, Eli N; Lawrence, Janna C; Hartley, Michael; Schweizer, Marin L
Abstract: The 2014–2016 Ebola epidemic in West Africa provided an opportunity to improve our response to highly infectious diseases. We performed a systematic literature review in PubMed, Cochrane Library, CINAHL, EMBASE, and Web of Science of research articles that evaluated benefits and challenges of hospital Ebola preparation in developed countries. We excluded studies performed in non-developed countries, and those limited to primary care settings, the public health sector, and pediatric populations. Thirty-five articles were included. Preparedness activities were beneficial for identifying gaps in hospital readiness. Training improved health-care workers' (HCW) infection control practices and personal protective equipment (PPE) use. The biggest challenge was related to PPE, followed by problems with hospital infrastructure and resources. HCWs feared managing Ebola patients, affecting their willingness to care for them. Standardizing protocols, PPE types, and frequency of training and providing financial support will improve future preparedness. It is unclear whether preparations resulted in sustained improvements. Prospero Registration . CRD42018090988. Abstract : Ebola preparation in developed countries was useful in identifying gaps in hospital readiness. Issues related to personal protective equipment procedures, hospital infrastructures, resources, and health-care workers' perceptions towards highly infectious diseases should be addressed to prepare for future epidemics.